Atitudes de discentes de administração da UFPI em relação à formação em métodos quantitativos: mensuração e análise de efeitos psicométricos - Miranda Filho, Francisco Tavares de (2021)
The general objective of this thesis was to develop a metric capable of measuring attitudes of students from Brazilian public universities in relation to quantitative methods to assess quantitative training in face-to-face and distance learning of UFPI Administration students. This research is structured in two studies, both of a theoretical-methodological nature. The first of them was developed during the month of December 2019 with Administration students from UFPB and UFPI, with a first sample of 158 respondents, of which 131 had already taken quantitative methods disciplines, and in a second sample (with all public universities) in April and May 2021, with 330 respondents, whose main objective was to develop a multi-item scale to measure the attitudes of students from Brazilian public universities in relation to quantitative methods in courses in Administration and , then propose a simplified single-item scale, identifying the factors that are related to the measurement process, especially those related to performance in the disciplines and in the course as a whole. The multiple-item scale was completed with a total of 15 indicators, four for perceived difficulty, six for personal enthusiasm and five for perceived importance. The first study innovated by presenting two metric options, one for more detailed evaluation and one for shorter evaluation. The second study, carried out from June to August 2021, had a sample of 193 respondents, 69 from the distance education modality and 124 from face-to-face teaching. Its main objective was to comparatively analyze the attitudes of UFPI Administration students in relation to quantitative methods in the modalities of presential and distance learning. In methodological terms, it was a descriptive and quantitative research. Data were analyzed using descriptive measures and psychometric quality analysis techniques. The results showed that there were no significant differences between the teaching modalities with regard to attitudes and general performance (measured by the academic performance index), but there were no significant differences in terms of mastery level, observing, in general, that students from the classroom modality declare a greater mastery of knowledge in Mathematics and Statistics. The research has brought contributions to the educational, academic and professional fields, as its studies have shown, through psychometric and multivariate analyses, the usefulness for higher education institutions, especially for undergraduate teaching in Administration at UFPI (in person and EaD).